How successful is the College of Health Sciences, Kuwait, in reducing dependence on expatriates? - Al-Ali, Salah (Technium Social Sciences Journal, 2021)
The importance of technical and vocational education in enhancing student’s capabilities, reducing unemployment level among youth, increase work wages, reduce poverty, and create an aspiration and hope among youth is highly noted in related literature. The image that technical and vocational education is considered as low-quality education for those who fail to be accepted in higher education is start to vanish. It is a creditable and certified type of education and cost less comparing to enrolling in a higher education institution. In fact, the ability to be employed in higher now comparing to a university degree holder. Industries and business require urgent semi and skilled manpower able to deal with the rapid change in technological changes, particularly those dealing with diversity production techniques. Kuwait as one of the gulf states, lack the availability of semi and skilled manpower in most of the countries sector. In governmental hospitals, the lack of national specialist in medical laboratory, dental care, and natural sciences is pharmaceutical is highly noted. As a result, the government has realized the importance of encouraging Kuwaiti to enroll in the College of Health Sciences with the hope to reduce dependence on expatriates. The research paper focuses on identifying and examining the perception of students at the College of Health Sciences, CHS, towards the quality of teaching and learning. In addition to, examining the perception of the CHS graduates direct supervisor in the health sector towards the standard of the filed training program, and the quality CHS graduates. The research is based on extensive field work that encompasses a review of the related literature, questionnaires, and an interview with a sample of heads of departments at the CHS. Interviews were also conducted with the CHS graduates’ direct supervisor in the health sector. Finally, the research will argue that unless the CHS recognize and appreciate the value of building a strong linkage with the health sector, its contribution in tackling the shortage of skilled and semi-skilled indigenous health care specialist will be below the government expectations, thus continuing relaying on expatriates for years ahead.